An analysis of problems arising out of English medium instruction of pupils in ten Ciskeian schools, with particular reference to geography in standard eight - Weimann, Alan Gilbert (Rhodes University, Faculty of Education, Department of Education, 1987)
Pupils in the Republic of South Africa in the T.B.V.C. States (Transkei, Bophuthatswana, Venda and Ciskei) are expected to commence study in all school subjects, except the first language (Xhosa, Tswana, Venda etc.) and the third language (Afrikaans), through the medium of English at the Std 3 level. English thus is the official medium of instruction for the greater part of the pupil's school experience. All examinations in all subjects (except those mentioned above) are set and answered through the medium of English. School textbooks from Std 3 upwards, in all subjects, are written in English. It is fairly safe to assert, therefore, that English should be the language life of the Higher Primary and Secondary School classroom. In 1953 a UNESCO report of proceedings of a conference held in 1951 maintained that the best medium for teaching a pupil was that of the mother-tongue. The report pleaded for mother-tongue instruction to be extended to as late a stage as possible in a pupil's school life (UNESCO 1953). While such a plea may be grounded on sound psychological and pedagogical reasoning, it is often ignored because of the realities existing within the educational system. The R.S.A. and the T.B.V.C. states are a case in point for as I have already mentioned, examinations, textbooks, and for that matter tertiary education at the post-matriculation level, all employ English as instructional medium. Pragmatism carries the day and the black pupil is compelled to use English. Other factors applicable to the South African context are the existence of many different ethnic groups, each with its own language, and the fact that a shortage of qualified and experienced teachers in many subjects and different levels within the schools has meant that often teachers whose first language is English are involved in teaching pupils from these various language groups
Keywords: Geography -- Study and teaching (Secondary) -- South Africa -- Ciskei; Language and education -- South Africa -- Ciskei; Native language and education -- South Africa -- Ciskei; Students, Black -- Education -- South Africa -- Ciskei; Language arts -- South Africa -- Ciskei